2016
DOI: 10.1007/s10751-016-1284-7
|View full text |Cite
|
Sign up to set email alerts
|

Some notes on data analysis for nuclear resonant inelastic x-ray scattering

Abstract: Nuclear Resonant Inelastic X-ray Scattering (NRIXS) is a spectroscopy method to study atomic vibrations and dynamics, currently done with synchrotron radiation at a few high energy third generation facilities. It finds a wide range of applications in condensed matter physics, materials science, chemistry, biophysics, geosciences, and high-pressure researches. Many atomic dynamics and lattice thermodynamics information can be derived from NRIXS measurements. Phonon Density of States (DOS) characterizes lattice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, in NRVS, the recoil fraction is analyzed, providing information on the ligand coordination of 57 Fe nuclei . An important advantage of this technique is that only vibrational modes containing significant 57 Fe motion are observed, and the extent of 57 Fe motion is proportional to the signal intensity. This makes the technique complementary to infrared and/or resonance Raman spectroscopies since modes that are not observed in these techniques may be observed in NRVS. The NRVS experimental data measured for precursor 1 , Int I and Int II (Figure S27, and Table S9, SI) are in line with those obtained from rR (Figure S26, SI).…”
Section: Experimental and Spectroscopic Resultsmentioning
confidence: 99%
“…However, in NRVS, the recoil fraction is analyzed, providing information on the ligand coordination of 57 Fe nuclei . An important advantage of this technique is that only vibrational modes containing significant 57 Fe motion are observed, and the extent of 57 Fe motion is proportional to the signal intensity. This makes the technique complementary to infrared and/or resonance Raman spectroscopies since modes that are not observed in these techniques may be observed in NRVS. The NRVS experimental data measured for precursor 1 , Int I and Int II (Figure S27, and Table S9, SI) are in line with those obtained from rR (Figure S26, SI).…”
Section: Experimental and Spectroscopic Resultsmentioning
confidence: 99%
“…Nuclear resonance vibrational spectroscopy (NRVS) has become a popular technique for elucidating the element-selective normal modes of appropriate Mössbauer isotopes. In previous work on the Cr HydA1 and Dd HydAB (from Desulfovibrio desulfuricans ) enzymes, we have shown that 57 Fe d –H h bending modes can be observed using 57 Fe-NRVS for the H hyd species and that these modes exhibit peak positions that are characteristic of the local environment. To better identify additional normal modes of H hyd , we proceeded to label the [2Fe] H subcluster not only with 57 Fe but also with 13 C and D in the methylene groups of the ADT ligand.…”
mentioning
confidence: 99%